EVOLUSI PASAR MENURUT PEMIKIRAN IMAM AL GHAZALI - Dwi Cahyono Kuntoro (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2019)
Al-Ghazali in developing the economy especially in the problem of market evolution departs from the principles of ketauhidan, akhirat, and minutes. From this principle developed multidimensional economic goals. Not only aimed at material-oriented but also in order to achieve spiritual satisfaction. In detail described al-Ghazali that the creation of the evolution of the market, namely